2017
DOI: 10.1093/neuonc/nox105
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of dacomitinib, a pan–human EGFR tyrosine kinase inhibitor, in recurrent glioblastoma patients with EGFR amplification

Abstract: Dacomitinib has a limited single-agent activity in recurrent GB with EGFR amplification. The detailed molecular characterization of the 4 patients with response in this trial can be useful to select patients who could benefit from dacomitinib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 32 publications
1
77
0
1
Order By: Relevance
“…Considering this aspect, immunotherapies may possibly outperform small molecule-based approaches. Despite the wide availability of TKIs clinically approved in oncological treatment, none of these inhibitors is used as a standard approach in GB treatment [64,72,77,179]. As EGFR vIII is a key oncogene with kinase activity-dependent function, it seems reasonable to consider whether the efficacy of TKI-based therapies should not be greater, especially since it has been postulated that the bloodbrain barrier in advanced GB is disrupted and thus should not enable for crossing of small molecules [180].…”
Section: Journal Of Oncologymentioning
confidence: 99%
“…Considering this aspect, immunotherapies may possibly outperform small molecule-based approaches. Despite the wide availability of TKIs clinically approved in oncological treatment, none of these inhibitors is used as a standard approach in GB treatment [64,72,77,179]. As EGFR vIII is a key oncogene with kinase activity-dependent function, it seems reasonable to consider whether the efficacy of TKI-based therapies should not be greater, especially since it has been postulated that the bloodbrain barrier in advanced GB is disrupted and thus should not enable for crossing of small molecules [180].…”
Section: Journal Of Oncologymentioning
confidence: 99%
“…Recent pre-clinical data suggest that dacomitinib effectively blocked the growth of EGFR amplified and/or EGFR mutant glioblastoma cells in vitro and in intracranial xenografts [21] , [22] . Moreover, dacomitinib has shown promise for the treatment of non-small cell lung cancer, squamous cell carcinoma of the head and neck, and in a subset of glioblastomas [23] , [24] , [25] , [26] . The effects of dacomitinib on medulloblastoma or pineoblastoma cell growth have not been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…TrkB-containing exosomes promote the transfer of aggressiveness between GBM cells (Pinet et al 2016). EGFR inhibition has been proposed as a therapeutic strategy in GBM and has been tested in preclinical (Buendia Duque et al 2019;Parker et al 2013;Zahonero et al 2015) and clinical (Makhlin et al 2019;Sepúlveda-Sánchez et al 2017), with mixed results. One previous study examined the interaction between TrkB and EGFR in experimental GBM and showed that stimulation of neurotrophin signaling can overcome the inhibitory effects of EGFR inhibition on GBM cell growth (Lawn et al 2015).…”
Section: Discussionmentioning
confidence: 99%